Fracture properties of concrete exposed to different sulfate solutions under drying-wetting cycles. (1st May 2022) - Yin, Yangyang; Hu, Shaowei; Lian, Jijian; Liu, Run
Highlights: The fracture properties of concrete subjected to drying-wetting cycles in different types of sulfate solutions were investigated. With the proposed method, the fracture toughness and the evolution of FPZ were studied. The horizontal strain and displacement fields in the FPZ obtained by the DIC technique were analyzed. Abstract: The fracture properties of concrete subjected to drying-wetting cycles in different types of sulfate solutions were investigated. Five exposure conditions, i.e. 5% and 10% sodium sulfate solutions, 5% and 10% magnesium sulfate solutions (by mass) and water were prepared. Three-point bending tests were carried out at the corrosion periods of 1, 2, 3, 5, 9 and 15 months with the digital image correlation (DIC) technique. The initial and unstable fracture toughness were calculated by the proposed method, and the evolution of the fracture process zone (FPZ) was studied. Results indicate that (1) with the increase of corrosion time, an initial increase stage and a followed decrease stage for the fracture toughness were noticed. The values of unstable fracture toughness obtained by the analysis method agreed well with those obtained by the experimental method. (2) The FPZ length increased linearly with the crack propagation until a full FPZ development, and then decreased gradually. The maximum FPZ length decreased slightly with the corrosion time. (3) Using DIC technique, the fracture path can be easily identified from the horizontal strain field, and the evolution of the FPZ can be determined by the horizontal displacement with high accuracy.